Architects of nature: growing buildings with bacterial biofilms. Issue 5 (16th August 2017) - Dade‐Robertson, Martyn; Keren‐Paz, Alona; Zhang, Meng; Kolodkin‐Gal, Ilana
Summary: In his text ' On Architecture', Vitruvius suggested that architecture is an imitation of nature. Here we discuss what happens when we begin using nature in architecture. We describe recent developments in the study of biofilm structure, and propose combining modern architecture and synthetic microbiology to develop sustainable construction approaches. Recently, Kolodkin‐Gal laboratory and others revealed a role for precipitation of calcium carbonate in the maturation and assembly of bacterial communities with complex structures. Importantly, they demonstrated that different secreted organic materials shape the calcium carbonate crystals formed by the bacterial cells. This provides a proof‐of‐concept for a potential use of bacteria in designing rigid construction materials and altering crystal morphology and function. In this study, we discuss how these recent discoveries may change the current strategies of architecture and construction. We believe that biofilm communities enhanced by synthetic circuits may be used to construct buildings and to sequester carbon dioxide in the process. Abstract : Biofilms formed by soil bacteria evolved to deal with the challenges of carbon dioxide emissions from cellular respiration, and to self‐renew following load stresses. Using Microbiology and Synthetic Biology we can now use the natural solutions bacteria found for the architectural "tool box" of the future.